Effect of window width on the fire speed spread in high-rise buildings - Ismail, Raya Haqqi; Kharufa, Omar Hazim (Journal of engineering sciences and information technology, 2023)
To improve and develop methods of design, and fire protection, architects, and engineers in the fields of protection face great challenges to reduce the loss of life, and property resulting from the outbreak of fires in buildings, especially high-rise buildings. Therefore, this study presented an explanation of the effect of window width, which could be an effective factor in the spread of fire, and its speed of transmission in high-rise buildings. The fire spread vertically by simulating its propagation characteristics in a 12-story building systematically by using the pyrosim program. Simulation results showed that the lowest speed of fire spread was 2 floors per minute in the model with windows 1.75 m wide. The risk of fire spreading in high-rise buildings decreases as the window width decreases, and vice versa. The study can contribute to choosing the optimal design alternative in terms of the speed of fire spread according to the width of the windows.